2014
DOI: 10.1111/vop.12151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two handheld applanation tonometers and the association of central corneal thickness, age, and intraocular pressure in normal and diseased canine eyes

Abstract: The AccuPen(®) measurements were slightly but significantly lower than the Tono-Pen XL(®) measurements in both normal and diseased canine eyes. The CCT affected the results of neither tonometer regardless of disease, while both IOP and CCT tended to decrease with age in normal eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
(117 reference statements)
3
14
1
1
Order By: Relevance
“…Former clinical trials using two different applanation tonometers in dogs determined that IOP tended to decrease with age (7,13). Similar results were obtained in a study on Anatolian buffaloes (28).…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…Former clinical trials using two different applanation tonometers in dogs determined that IOP tended to decrease with age (7,13). Similar results were obtained in a study on Anatolian buffaloes (28).…”
Section: Methodssupporting
confidence: 74%
“…The statistical evaluation showed no difference between the means for the two age groups obtained by both devices. The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP.…”
Section: Methodscontrasting
confidence: 54%
“…The effect exerted by CCT on IOP was found to differ between the TonoPen XL and TonoVet tonometers, and IOP values were shown to increase by 1 and 2 mmHg, respectively, for every 100 μm increase in CCT . However, other studies have found no correlation between CCT and IOP in dogs …”
Section: Introductionmentioning
confidence: 84%
“…One study demonstrated that for every 100µm increase in central corneal thickness in normal dogs there was an elevation of 1mmHg in IOP using applanation tonometry (Park et al 2011). However, another study demonstrated that central corneal thickness did not affect applanation tonometry (Kato 2014). Other viscoelastic properties of the cornea such as corneal hysteresis and corneal resistance factor can also alter IOP readings in humans (Liu and Roberts 2005).…”
Section: Discussionmentioning
confidence: 99%